Komunikasi sebagai Resolusi Konflik dan Proses Pengambilan Keputusan - Fifi Hasmawati (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2020)
In organizations people who work in groups work to develop their skills and perspectives, which sometimes have differences about the work / duties with the work / tasks of other groups. When interactions between them occur, then conflict becomes the potential to arise. In organizational life at any time conflicts can occur in the form of conflicts between individuals as members of the organization, as well as conflicts between members and the organization. Conflict conditions are not favorable for leadership because it will cause various difficulties in moving members to work together, in an effort to achieve common goals. In this condition member participation not only decreases, but also evades and challenges as a sign of lacking or ineffective leadership. Conflicts encourage individuals to look for friends to show their self-solidarity and problems, so there are groupings of members that contradict others, both openly and secretly